Menumbuhkan Kedisiplinan Siswa MTs Al-Amien Kota Kediri melalui Pembiasaan Sholat Dhuha - Agus Dwi Santosa; Sabudin Yusoh; Agus Subandono; Ahmad Aly Syukron Aziz Al Mubarok; Agus Miftakus Surur (Edudeena : Journal of Islamic Religious Education, 2022)
Abstract: Discipline is one of the characters that must be possessed by students, so it needs to be trained and accustomed to students, especially when in the school environment. To familiarize discipline, one of which is the Dhuha prayer in congregation, the Duha prayer was chosen because in addition to training students to practice the sunnah of the Dhuha prayer, it can also be used as a discipline habituation tool. The method used is a qualitative method using interview data, observation data, and documentation. The results of the study showed that in the implementation of the dhuha prayer in congregation there were several obstacles experienced, especially at the beginning of the implementation of this obligation. Among them are the age of the students who are still small, who have just graduated from elementary school and their backgrounds are mostly graduates from formal schools, so it is still rare to be able to perform this dhuha prayer. In the end, the implementation and habituation of prayer was able to improve the discipline of the students. Not only in the implementation of the dhuha prayer but also in other matters such as going to school, studying, reading Quran or others. Abstrak: Disiplin merupakan salah satu karakter yang harus dimiliki oleh peserta didik, sehingga perlu dilatihkan dan dibiasakan kepada siswa terutama ketika di lingkungan sekolah. Untuk membiasakan kedisiplinan salah satunya dengan kegiatan sholat Dhuha berjamaah, sholat Dhuha dipilih karena selain melatih siswa untuk mengamalkan amalan sunah Sholat Dhuha, juga dapat digunakan sebagai alat pembiasa disiplin. Metode yang digunakan adalah metode kualitatif dengan menggunakan data hasil wawancara, data hasil observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa dalam pelaksanaan kegiatan sholat dhuha secara berjamaah ada beberapa kendala yang dialami, terutama pada awal diterapkannya kewajiban ini. Diantaranya adalah usia para siswa yang masih kecil yaitu baru lulus SD dan latar belakang mereka yang kebanyakan lulusan dari sekolah formal sehingga masih jarang yang bisa melakukan sholat dhuha ini. Pada akhirnya, dari pelaksanaan dan pembiasaan sholat mampu meningkatkan kedisiplinan para siswa. Tidak hanya dalam pelaksanaan sholat dhuha saja tetapi juga dalam hal-hal lainnya seperti berangkat sekolah, belajar, mengaji ataupun yang lainnya.